Dietary soy isoflavones increased hepatic protein disulfide isomerase content and suppressed its enzymatic activity in rats. (June 2014) - Xiao, Chao Wu; Donak, Kevin; Ly, Olivia; Wood, Carla; Cooke, Gerard; Curran, Ivan
Protein disulfide isomerase (PDI) is a multifunctional protein and plays important roles in protein folding, triglyceride transfer, insulin degradation, and thyroid hormone transportation. This study examined the modulation of PDI expression by soy consumption using rat as a model. Sprague-Dawley male and female rats at 50 days (d) of age were fed diets containing either 20% casein or alcohol-washed soy protein isolate (SPI, containing 50 mg isoflavones (ISFs)/kg diet) or SPI plus ISF (250 mg/kg diet) and mated at age of 120 d. The offspring (F1) were fed the same diets as their parents. Addition of ISF to SPI diet markedly increased PDI protein content in the liver and testis of the adult rats compared with the casein or SPI diet. PDI mRNA abundance in the liver and protein content in the brain, thyroid, heart, and uterus were unchanged by the diets. Two-dimensional Western blot showed that the rats fed diets containing SPI had a diminished hepatic PDI protein with an isoelectric point (pI) of 6.12, a dephosphorylated form, compared with the rats fed diets containing either casein or SPI with supplemental ISF. Soy ISF added into SPI diet remarkably suppressed hepatic PDI activity of the rats compared with the casein diet. Moreover, soy ISF dose-dependently increased PDI and thyroid hormone receptor (TR) β protein content, whereas reduced TR DNA binding ability in human hepatocytes. Overall, this study shows that soy ISF increased hepatic PDI protein content, but addition of ISF into SPI diet inhibited its enzymatic activities and this effect may be mediated through a post-transcriptional mechanism.